Emergence and Transmission of Daptomycin and Vancomycin-Resistant Enterococci Between Patients and Hospital Rooms. (9th January 2021) - El Haddad, Lynn; Hanson, Blake M; Arias, Cesar A; Ghantoji, Shashank S; Harb, Cynthia P; Stibich, Mark; Chemaly, Roy F
Abstract: Background: Vancomycin-resistant enterococci (VRE) are a major cause of morbidity and mortality in immunocompromised patients. Tracking the dissemination of VRE strains is crucial to understand the dynamics of emergence and spread of VRE in the hospital setting. Methods: Whole genome sequencing (WGS) and phylogenetic analyses were performed to identify dominant VRE strains and potential transmission networks between 35 patients with VRE-positive rectal swabs and their rooms (main rooms and bathrooms) on the leukemia (LKM) and the hematopoietic cell transplant (HCT) floors. Sequence types (STs), drug resistance genes, and patients' outcomes were also determined. Results: A total of 89 VRE strains grouped into 10 different STs, of which newly described STs were isolated from both floors (ST736, ST494, ST772, and ST1516). We observed highly genetically related strains transmitted between rooms, floors, and time periods in an average period of 39 days (ranging from 3 to 90 days). Of 5 VRE bacteremia events, 3 strains were lacking the pili operon fms14–17–13 (ST203) and the remaining 2 were resistant to daptomycin (DAP; ST736, ST664). Of 10 patients harboring DAP-resistant strains, only 2 were exposed to DAP within 4 months before strain recovery. Conclusions: Our comparisons of VRE strains derived from the environment and immunocompromised patients confirmed horizontal transfer of highly related genetic lineages of multidrug-resistant (particularly to DAP) VRE strains between HCT and LKM patients and their room environment. Implementing WGS can be useful in distinguishing VRE reservoirs where interventions can be targeted to prevent and control the spread of highly resistant organisms. Abstract : We observed highly genetically related strains transmitted vancomycin-resistant enterococci (VRE) strains between distinct rooms, floors, and time periods in an average period of 39 days. Ten patients had daptomycin (DAP)-resistant strains, but only 2 were exposed to DAP.